2013
DOI: 10.9735/0975-3710.5.1.330-338
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Parameters of Soybean Cultivars as Influenced With Seed Storage Periods, Conditions and Materials

Abstract: This investigation was elucidated seedling characters effects of soybean cultivars i.e. Crawford, Giza 111, Giza 21, Giza 22 and Giza 35 due to ageing (storage) in different packaging material i.e. seeds or pods in plastic or cloth bags for different periods i.e. 3, 6, 9 and 12 months under ambient and refrigerator conditions. Seedling parameters i.e. root and shoot length, seedling fresh and dry weight root/shoot ratio and seedling vigor index were decreased with the period of ageing. Soybean cultivars are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
2
3
0
2
Order By: Relevance
“…Root length of control groups mostly existed in a range of 18-22.7 cm, while in long-term storage most of the cultivars in terms of root length were accumulated. A similar result was also reported a decline in root length of maize with increasing aging duration (Kandil et al, 2013).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Root length of control groups mostly existed in a range of 18-22.7 cm, while in long-term storage most of the cultivars in terms of root length were accumulated. A similar result was also reported a decline in root length of maize with increasing aging duration (Kandil et al, 2013).…”
Section: Resultssupporting
confidence: 81%
“…In the present study, Alpaslan and Zencirci 2002 were ranked low and high for shoot mass in both long-term storage and control, respectively. A close look at the data in Table 2 suggested that average shoot mass was declined by long-term storage with 0.14 g compared to control with 0.17 g. The results were confirmed by results of Kandil et al (2013) that indicated a decline in root length, shoot length, and shoot mass through long-term storage in soybean.…”
Section: Resultssupporting
confidence: 51%
“…Root length and dry weight difference may be due to genetic differences and biochemical composition of each variety causing differences in deterioration rate and decreased vigor (Kandil et al, 2013). High dry weights showed that the use of reserves in the seed is very efficient because the seeds that have a high vigor can transmit raw materials to the embryo shaft quickly so that the accumulation of dry weight increases.…”
Section: The Effect Of Differentmentioning
confidence: 99%
“…dry weight of normal seedlings, the speed of germination and total normal seedlings decrease could be seen in Figure 2. Kandil et al (2013) reported that root length, shoot length and dry weight of normal seedling decreased after being stored for 12 months when compared to the 3,6, and 9 months stored period of soybean seeds Increased storage period on seed wheat from storage of 3,6 and 9 months significantly affect the viability and quality of seeds, the germination percentage was lowest in 9 months.…”
Section: Monthsmentioning
confidence: 99%
See 1 more Smart Citation